Privatization of state owned enterprises: arguments and perceptions: the case of TAP and its privatization - Rodrigues, Joana Isabel do Deserto Dias (2017)
Despite being one of the major economic phenomena in recent history, privatization causes received relatively little attention in analysis until quite recently. This qualitative paper summarizes the causes that led to the privatization of state-owned enterprises, with the specific case of TAP Portugal being analyzed. For a better comprehension of the theme, the characteristics and the context of state enterprises creation, as well as the privatization movement and its impacts, were analyzed as well. The general objective of the study is to understand if there are differences between the motivations to privatize and the expectations that TAP Portugal executives and workers have on the matter, therefore using TAP Portugal as the case study to support the analysis. Some interviews were performed to TAP Portugal executive members and workers, and results show that, privatization causes and TAP’s members’ expectations are aligned in some motivations. The intervention of external organisms in managing state enterprises, the necessity of reduction of public sector borrowing requirement, the limited access to capital, the ineffective state administration, bureaucracy concerns, management conditions, lack of investment capacity and the role of the state, are the main conclusions that led TAP to be privatized.